Preface to the special issue on the 12th Workshop on Programming Language Approaches to Concurrency and Communication-Centric Software (PLACES) 2020 - Balzer, Stephanie; Padovani, Luca (Journal of logical and algebraic methods in programming, 2022)
This volume contains the JLAMP special issue on the twelfth edition of the workshop on Programming Language Approaches to Concurrency and Communication-cEntric Software (PLACES 2020). The articles cover topics ranging from the semantics of communicating systems, to static and dynamic analysis techniques for session-based communications, to information flow analysis in heterogeneous organisations.